2014
DOI: 10.5424/sjar/2014121-4340
|View full text |Cite
|
Sign up to set email alerts
|

Development of virulence to Meloidogyne incognita on resistant pepper rootstocks

Abstract: The root-knot nematode (RKN) Meloidogyne incognita is a major soil parasite of pepper crops in greenhouses in Southeast Spain. Due to the limitations of the use of soil fumigants, grafting plants on resistant rootstocks (R-rootstocks) has become an important alternative to chemical nematicides. The repeated use of R-rootstocks can bring about the selection of virulent populations capable of overcoming resistance. We carried out a six-year investigation on resistant rootstocks in a naturally M. incognita infest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
1
15
0
6
Order By: Relevance
“…Me1 demonstrated a high and durable resistance, while the resistance of Me3 was less pronounced and shorter lived, regardless of the genetic background around these R‐genes. These observations coincide with those of previous studies carried out in laboratory (Castagnone‐Sereno, Bongiovanni, Palloix, & Dalmasso, ; Djian‐Caporalino et al., ), and with those obtained under field and greenhouse conditions (Djian‐Caporalino et al., ; Ros‐Ibáñez et al., ). In these works, the appearance of nematode populations virulent to Me3 but not Me1 was observed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Me1 demonstrated a high and durable resistance, while the resistance of Me3 was less pronounced and shorter lived, regardless of the genetic background around these R‐genes. These observations coincide with those of previous studies carried out in laboratory (Castagnone‐Sereno, Bongiovanni, Palloix, & Dalmasso, ; Djian‐Caporalino et al., ), and with those obtained under field and greenhouse conditions (Djian‐Caporalino et al., ; Ros‐Ibáñez et al., ). In these works, the appearance of nematode populations virulent to Me3 but not Me1 was observed.…”
Section: Discussionsupporting
confidence: 92%
“…() observed an increase in nematode infections in three consecutive growing seasons of plants carrying Me1 . In the case of Me3 , previous studies have clearly demonstrated the development of virulence in avirulent populations of M. incognita when there is strong pressure of Me3 , both in laboratory conditions (Castagnone‐Sereno et al., ) and in greenhouse‐grown pepper (Ros‐Ibáñez et al., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For more than 70 years now, although some other R genes have been identified in the wild tomato S. peruvianum , Mi‐1.2 has been the only source of resistance in tomato production against RKNs. Clearly, the extensive use of the same R gene at a large scale may result in the emergence and spread of virulent nematode populations able to overcome it, and Mi‐1.2 ‐resistance‐breaking populations in tomato have been discovered, as have N ‐ and Me3 ‐resistance‐breaking populations in pepper . Such ability to overcome plant resistance may thus constitute a severe limitation for RKN control.…”
Section: Practical Limitations Of the Use Of Natural R Genes In Solanmentioning
confidence: 99%
“…Regarding pepper, the selection for virulence to the Me3 gene has been reported after two consecutive pepper crops grafted onto the rootstock cv. Atlante (Ros‐Ibáñez et al , ). In relation to the N gene, virulence has been reported in the USA but without any information on the selection process (Thies, ).…”
Section: Discussionmentioning
confidence: 99%